Defining the Interactions and Role of DCAF1/VPRBP in the DDB1-Cullin4A E3 Ubiquitin Ligase Complex Engaged by HIV-1 Vpr to Induce a G(2) Cell Cycle Arrest - Gérard, Francine C. A. (Public Library of Science, 2014)
HIV viral protein R (Vpr) induces a cell cycle arrest at the G(2)/M phase by activating the ATR DNA damage/replication stress signalling pathway through engagement of the DDB1-CUL4A-DCAF1 E3 ubiquitin ligase via a direct binding to the substrate specificity receptor DCAF1. Since no high resolution structures of the DDB1-DCAF1-Vpr substrate recognition module currently exist, we used a mutagenesis approach to better define motifs in DCAF1 that are crucial for Vpr and DDB1 binding. Herein, we show that the minimal domain of DCAF1 that retained the ability to bind Vpr and DDB1 was mapped to residues 1041 to 1393 (DCAF1 WD). Mutagenic analyses identified an α-helical H-box motif and F/YxxF/Y motifs located in the N-terminal domain of DCAF1 WD that are involved in exclusive binding to DDB1. While we could not identify elements specifically involved in Vpr binding, overall, the mutagenesis data suggest that the predicted β-propeller conformation of DCAF1 is likely to be critical for Vpr association. Importantly, we provide evidence that binding of Vpr to DCAF1 appears to modulate the formation of a DDB1/DCAF1 complex. Lastly, we show that expression of DCAF1 WD in the absence of endogenous DCAF1 was not sufficient to enable Vpr-mediated G(2) arrest activity. Overall, our results reveal that Vpr and DDB1 binding on DCAF1 can be genetically separated and further suggest that DCAF1 contains determinants in addition to the Vpr and DDB1 minimal binding domain, which are required for Vpr to enable the induction of a G(2) arrest.